(Re)Positioning Humanities in the Malaysian Higher Education Landscape (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper discusses the humanities and humanities education, which is inevitably embedded in the context of a re-assessment of the role and functions of universities in the current and future Industry 4.0 environment. While the humanities are generally considered as an embattled field since the emphasis on science and technology subjects in many developed and emerging economies, this paper does not subscribe to the notion of the humanities being handcuffed to a crisis narrative that are incomplete and disabling its future potentials. In the Industry 4.0 environment and perhaps an equivalent Society 4.0, there would be a dire need for society to envision a plan that would give top priority to the potential benefits of a higher education based on human-technology convergence. Failure to do so would mean humans would be overwhelmed by robotics and artificial intelligence (AI), peripheralising any disciplines that are considered as not relevant. In the context of Malaysia, the paper unpicks the issues and challenges in the provision of humanities education in the higher education landscape that begin to acknowledge and reclaim values and the human outcome in the higher education system still in the nascent stage of realising the importance of framing policies in the context of the human-technology convergence. This paper concludes by suggesting the way forward in re-positioning the humanities and humanities education, which would contribute to the idea of humanising higher education in the context of Industry 4.0.